A novel modification of carbon nanotubes for improving the electrical and mechanical properties of polyethylene composites. (April 2019) - Peng, Bo; Jiang, Yunlong; Zhu, Aiping
Abstract: A simple and effective method, modifying MWCNTs with cationic waterborne epoxy emulsion, was developed to improve the dispersion of multi-walled carbon nanotubes (MWCNTs) and enhance the interfacial interaction between matrix and the filler. The dispersion of mMWCNTs in polymer was characterized by Scanning Electron Microscope and Transmission Electron Microscope. Rheological analysis revealed that better mMWCNTs network in PE matrix was developed at a lower content of MWCNTs as compared with that of unmodified MWCNTs, which resulting in a lower percolation threshold and improved electrical conductivity of mMWCNTs/PE. Moreover, the PE nanocomposite with uniformly dispersed mMWCNTs has better mechanical properties than those of MWCNTs/PE. Highlights: An effective and industrialized method to modify MWCNTs (mMWCNTs) was developed with cationic waterborne epoxy emulsion. The distribution of mMWCNTs in PE matrix has been improved significantly compared to MWCNTs. The percolation threshold of mMWCNT/PE composites is significantly decreased and the electrical conductivity is tremendously improved. When the loading of MWCNTs is 1 wt%, the mMWCNTs/PE composites not only meet the requirements of antistatic materials, but also the elongation at break of mMWCNTs/PE composites increase by 26.6%.